Perceived support and preparedness for the next pandemic among Israeli social workers in hospital settings during the COVID-19 pandemic. (21st April 2022) - Shinan-Altman, Shiri; Schiff, Miriam; Rosenne, Hadas; Chen, Wendy; Kaofer, Hanna; Zeevi, Sagit; Nir-Paz, Ran
ABSTRACT: This study describes the conditions under which Israeli social workers in hospital settings operated s during the COVID-19 pandemic, and assesses their perceived support (informal and organizational support) and preparedness for the next pandemic. It further assesses correlates for perceived support and associations between perceived support and preparedness. The participants were 163 social workers from four hospitals who completed an on-line survey. The findings revealed that the level of exposure to COVID-19 and fear of contracting COVID-19 were unrelated to perceived informal and organizational support. Age and having children who are minors living at home moderated the relationship between fear of contracting COVID-19 and both types of perceived support. Each type of perceived support was significantly associated with preparedness beyond age, having minors at home, exposure to COVID-19, and fear of contracting COVID-19. Implications for research and practice are discussed.